The Effect of Elastic Deformation of Bearing Surface on The Steady State Performance of Offset Halves Bearing - Muhsin, Ibrahem A. (Nahrain University College of Engineering Journal, 2009)
In this research a theoretical study was presented to find the performance of the offset halves bearing which used in applications of high velocities ,like centrifugal machines, dentist tools and high precession machines. In studying the elastic deformation, three types of alloys have been used for coatingthe bearing surface. These alloys Cu-alloy, Alalloy and Mg-alloy. And these show that the bearing material has a considerable effect on the essential bearing characteristics. The bearing made of soft material has lower performance than that made of harder material. In this work the bearing performancewas investigated under the following conditions : 1-Elastohydrodynamic lubrication at a rotational velocity of 2000rpm and L/D ratios Of(0.5.)and (1)2-Elastohydrodynamic lubrication at a rotational velocity of 15000rpm and L/D ratios of 0.5and (1). The results of analysis show that the offset bearing deformation (elastic deformation) has a considerable influence on the performance at a high eccentricity values (n>0.9) i.e. under high loa